2022
DOI: 10.3389/fmed.2021.725118
|View full text |Cite
|
Sign up to set email alerts
|

[18F] Sodium Fluoride Dose Reduction Enabled by Digital Photon Counting PET/CT for Evaluation of Osteoblastic Activity

Abstract: The aim of the study was to assess the quality and reproducibility of reducing the injected [18F] sodium fluoride ([18F]NaF) dose while maintaining diagnostic imaging quality in bone imaging in a preclinical skeletal model using digital photon counting PET (dPET) detector technology. Beagles (n = 9) were administered three different [18F]NaF doses: 111 MBq (n = 5), 20 MBq (n = 5), and 1.9 MBq (n = 9). Imaging started ≃45 min post-injection for ≃30 min total acquisition time. Images were reconstructed using Tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…It should be noted that additional doses may be delivered to the patient from other procedures, for example, the computed tomography (CT) part of the PET‐CT scan, which will vary depending on the tube current and CT scan time. Studies have shown that it is possible to obtain a successful quantitative [ 18 F]NaF PET scan at the lumbar spine using an injected activity as low as 90 MBq, 13,14 and some researchers have proposed further dose reduction strategies in preclinical settings 41 . However, radiation dosimetry is a field in itself, and this topic will not be discussed here any further.…”
Section: Imaging Protocol For a Dynamic [18f]naf Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that additional doses may be delivered to the patient from other procedures, for example, the computed tomography (CT) part of the PET‐CT scan, which will vary depending on the tube current and CT scan time. Studies have shown that it is possible to obtain a successful quantitative [ 18 F]NaF PET scan at the lumbar spine using an injected activity as low as 90 MBq, 13,14 and some researchers have proposed further dose reduction strategies in preclinical settings 41 . However, radiation dosimetry is a field in itself, and this topic will not be discussed here any further.…”
Section: Imaging Protocol For a Dynamic [18f]naf Studymentioning
confidence: 99%
“…Studies have shown that it is possible to obtain a successful quantitative [ 18 F]NaF PET scan at the lumbar spine using an injected activity as low as 90 MBq, 13,14 and some researchers have proposed further dose reduction strategies in preclinical settings. 41 However, radiation dosimetry is a field in itself, and this topic will not be discussed here any further.…”
Section: Imaging Protocol For a Dynamic [ 18 F]naf Studymentioning
confidence: 99%